An art that obscures: Baderoon regarding Muslims - Rafudeen, Auwais (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Baderoon, Gabeba (2015) Regarding Muslims: From slavery to post-apartheid. Johannesburg: Wits University Press (2014). ISBN 978-1-86814-769-4 pbk. Pages xix + 207 “Praise be to God for making us forget”. These words, uttered by a White Helmets volunteer in Syria, is echoed in Gabeba Baderoon densely-layered Regarding Muslims in two ways. The shame of sexual violence and miscegenation associated with slavery at the Cape has led – and here Baderoon quotes Zoë Wicomb – to a “total erasure of slavery from folk memory” (p 88). But in a less salutary way, this forgetfulness is also characteristic of those who were the major beneficiaries of this institution. Colonists wished to forget slavery, and their representation of Cape Muslims – “Malays” – played a critical role in this forgetting. This is one of the main arguments that emerge from Baderoon’s book.